A. Rosminis anthropologische Begründung der Gesellschaft - Krienke, Markus (Zeitschrift für katholische Theologie, 2007)
Rosmini argued for an anthropological foundation of social institutions by combining scholastic thought with Kantian liberalism and went on to analyse modern thought on social contract, traditionalism, early socialism, and liberalism. Thus Rosmini became one of the forerunners of modern Christian social thought.